PERGULATAN BATIN SASANA DALAM NOVEL PASUNG JIWA KARYA OKKY MADASARI: KAJIAN PSIKOLOGI SASTRA - Dwi Faradylla Nur Khasanah; Dwi Mei Murtini; Titik Sudiatmi (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research examines the inner struggle in the novel "Pasung Jiwa" by Okky Madasari using a literary psychology approach. This novel tells the story of Sasana's life journey, which experiences deep inner conflict due to dissatisfaction with her identity and freedom. Sasana, who was born as a man, feels trapped in societal norms and expectations that shackle the expression of his identity. The analysis shows that Sasana experienced an identity crisis which led to the search for individual freedom, passing through various stages of the hierarchy of needs. Data collection in this research used reading, listening and note-taking techniques. The results of this research explain that the character Sasana in the novel "Pasung Jiwa" by Okky Madasari, which was studied using literary psychology, has psychological deviation factors, causes of deviation, and sociocultural factors. The psychological deviation factors experienced by Sasana include depression, anxiety and dissociative disorders. This research also reveals that Sasana deviation is influenced by cognitive and sociocultural factors that suppress individual freedom. In a sociocultural context, this novel reflects criticism of social norms that are rigid and do not provide space for the expression of individuality. The novel "Pasung Jiwa" not only offers a personal narrative but also a deep social reflection. Through a literary psychology approach, this research provides insight into the complexity of the human mind and the importance of individual freedom in a broader social context.